COMBINED EFFECT OF CAPTOPRIL AND THIAZIDE DIURETIC ON SERUM LIPID PROFILE IN HYPERTENSIVE WOMEN - Karim, Samina; Karim, Sabiha; Begum, Almas; Javed, Nasreen (Journal of Ayub Medical College Abbottabad, 2001)
Background: Hypertension has long been recognized as the major risk factor for the development of coronary disease. It was found that the combination of thiazide diuretic and ACE inhibitor has favorable antihypertensive and metabolic effect i.e the combination reduces the levels of lipid. Methods: 40 women aged between 35-60 years having systolic blood pressure equal to or greater then 160mmHg were included in the study. Captopril in a dose of 25-75 mg plus thiazide 25-50mg orally per day was given in divided doses. Before starting therapy and then after 4 and 10 week of therapy, 5ml of fasting blood was drawn to analyze lipid profile like serum triglyceride, cholesterol and lipoprotein (HDL and LDL-Cholesterol). Results: Study observed a marked decrease of blood pressure after taking captopril with diuretics. Level of triglyceride and of HDL and LDL-cholesterol were also significantly changed (P<0.01) as compared to their controls. Conclusion: It was observed that captopril in combination of thiazide diuretics not only decrease blood pressure but also a beneficial effect on lipid profile. Hence further research is needed on large number of patients of both sexes.